Genetic polymorphism in DNA base excision repair gene XRCC1among medical radiation workers - Harry Nugroho Eko Surniyantoro; Yanti Lusiyanti; Wiwin Mailana; Devita Tetriana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
X-rays repair cross-complementing group 1 (XRCC1) gene is one of the gene that plays an important role in base excision repair system (BER) and DNA repair both single and double strand breaks. Individuals with XRCC1 exon 10 (Arg399Gln) gene polymorphisms and carrying 399Gln allele variants (A allele) have a greater risk of DNA damage than their wildtype, 399Arg. The aim of this study was to examine the genotype frequencies of single nucleotide polymorphisms (SNPs) of XRCC1 exon 10 among medical radiation workers. This study involved 77 samples from several hospitals in Indonesia. Genotyping of XRCC1 exon 10 gene polymorphism was performed using PCR-RFLP. Individuals carryingA allele had lower frequency than that is carrying their wildtype of 399Arg (0.39 vs. 0.61). The results indicated that 39% of medical radiation workers had a risk of repair efficiency of DNA damage and might influence an individual's risk of cancer. Ionizing radiation induces many types of damage to DNA, requiring multiple repair pathways to restore genomics integrity. Other important genes/pathways, especially those for DNA double-strand break repair, might also play a role and should be further investigated. Furthermore, polymorphisms leading to inefficient DNA repair might also be associated with late reactions to radiotherapy.